Why Do Farmers Choose Auction Markets? Institutional and Socioeconomic Determinants of Red Chili Marketing Decisions in Indonesia - Irma Herawaty Sitorus; Rahmanta Rahmanta; Lindawati Lindawati (Baileo: Jurnal Sosial Humaniora, 2026)
This study examines the institutional and socioeconomic determinants of smallholder red chili farmers’ decisions to participate in auction markets rather than traditional markets in North Tapanuli Regency, Indonesia. Farmers’ marketing decisions are conceptualized as choices between competing market institutions rather than as responses to price incentives alone. The study employed an explanatory sequential mixed-methods design. Quantitative data were collected from 95 active red chili farmers in Siborong-borong District using purposive and snowball sampling techniques and analyzed with binary logistic regression to estimate the probability of auction market participation. The model was evaluated using goodness-of-fit statistics and odds ratio analysis. Qualitative data from in-depth interviews with farmers, traders, and market managers were used to explain the institutional mechanisms underlying farmers’ market choices. The results indicate that farm size and farming experience significantly increase the likelihood of auction market participation, whereas age, education, price perception, transportation availability, and farmer group activity do not have significant effects. These findings suggest that farmers’ market institution choices are driven primarily by structural capacity and institutional adaptation rather than price considerations. The study contributes to the literature by integrating smallholder market participation and institutional market choice within the context of institutional transition in Indonesia’s horticultural sector, offering policy insights for more inclusive auction market revitalization and rural socioeconomic development.